MODEL ANALISIS Z SCORE TERHADAP PREDIKSI KEBANGKRUTAN ( Studi pada PT Garuda Indonesia,Tbk tahun 2015-2017) - Arief Yuswanto Nugroho (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2018)
The purpose of this study was able to be used in predicting bankruptcy using the Altman Z-score analysis method. This research is quantitative descriptive. The object of this research is PT Garuda Indonesia Tbk with the year of observation 2015 to 2017. Data from this research are secondary data and data sources taken from the Indonesia Stock Exchange in the form of PT Garuda Tbk financial statements 2015 through 2017. The results of this research reveal that the variable X1 (working capital / Total Asset) in 2015 has a value of -0.047, in 2016 has a value of -0.0760 and in 2017 has a value of -0.1781. Variable X2 (retained earnings / total assets) in 2015 has a value of 0.00155, in 2016 has a value of 0.0013 and in 2017 has a value of 0.0013. Variable X3 (earning before interest and taxes / total assets) in 2015 has a value of 0.0057, in 2016 has a value of 0.0147 and in 2017 has a value of -0.1314. Variable X4 (market value equity / book value of total liabilities) in 2015 has a value of 1.442, in 2016 has a value of 1.442 and in 2017 has a value of 1.248. Variable X5 (sales / total assets) in 2015 has a value of 1,150, in 2016 has a value of 1,247 and in 2017 has a value of 1,105. For Z -Score value in 2015 has a value of 2.55, in 2016 has a value of 2.21 and in 2017 has a value of 2.04.. For the highest Z-Score number in 2015 is 2.55 and the lowest Z-Score is in 2017 at 2.04. Based on the results of the research it can be concluded that the Altman Z score method is able to answer bankruptcy predictions before 2 years the condition of corporate profits has decreased.